HUBUNGAN ANTARA PENGETAHUAN TENTANG PEMBANGUNAN BERKELANJUTAN, EMPATI DAN KOMITMEN TERHADAP LINGKUNGAN DENGAN TANGGUNG JAWAB PESERTA PROGRAM PARTICIPANTS RESPONSIBILITY PADA BANK RAKYAT INDONESIA DALAM PELESTARIAN LINGKUNGAN - Moch. Sjafaat Ismail (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2012)
The objective of the research is to find out the relationship between knowledge of sustainable development, emphaty, and commitment toward environment with development program partisipants responsibility of environmental preservation. The sampel of this research were 73 persons which randomly taken. The data were analyzed by using regression and correlation techicques. Findings of the research concluded: 1) there is positive correlation between knowledge of the sustainable development with development program partisipants responsibility of environment preservation, 2) there is positive correlation between emphaty with development program partisipants responsibility of environment preservation, 3) there is positive correlation between commitment toward environment with development program partisipants responsibility of environmental preservation, and furthermore 4) there are correlation between knowledge of the sustainable development, emphaty, and commitment toward environment with development program partisipants responsibility of environmental preservation. Based on this development program partisipants result of responsibility of environmental preservation enhanced by increasing knowledge of the sustainable development, emphaty, and commitment toward environment.